A NEW TECHNOLOGY FOR REMEDIATION OF CONTAMINATED SITES IN LOWLAND AREAS - Somasundaram Valliappan; Nasser Khalili; R. K. Niven (International Association of Lowland Technology, 2000)
A new in situ remediation, method, uplow washing, is describedin which contaminants are removed by an upward fluidizing flow of water and/or gas produced by a jet inserted into a granular contaminated formation. Contaminant removal is achieved by the buoyant release of NAPL droplets and elutriation of finer particles. Experiments on contaminant removal by fluidization within a controlled column indicate significant reductions in diesel levels (95-99,9%) may be achieved by gas-liquid uplow washing (GLUW), for a wide range of initial diesel concentrations (10,000 to 150,000 mg/kg) and for soil fines contents of zero to 10%. In uniform sands, the water and gas velocities exmined during GLUW have no significant bearing on diesel remediation efficiency, suggesting that water velocities may be reduced to a level at which the fluidized bed is largely gas-supported. Significant reductions in lead concentrations (59-88%) from soils containing 1,500-1,960 mg/kg precipitated lead may also be achieved by GLUW.